2013
DOI: 10.3732/ajb.1200648
|View full text |Cite
|
Sign up to set email alerts
|

The desert moss Pterygoneurum lamellatum (Pottiaceae) exhibits an inducible ecological strategy of desiccation tolerance: Effects of rate of drying on shoot damage and regeneration

Abstract: For the first time, a desert moss is shown to exhibit an ecological strategy of desiccation tolerance that is inducible, challenging the assumption that arid-land bryophytes rely exclusively on constitutive protection. Results indicate that previous considerations defining a slow-dry event in bryophytes need reevaluation, and that the ecological strategy of inducible desiccation tolerance is probably more common than currently understood among terrestrial bryophytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 90 publications
2
40
0
Order By: Relevance
“…This demonstrates the importance of the bryophytes' life form traits, as patch size and structure, in establishing a slow dehydration rate that allows for the possibility of inductive processes of DT. A number of recent studies have indicated that the ecological strategy of DT in bryophytes is largely inducible, including both aquatic (Cruz de Carvalho et al, 2011 and desert mosses (Stark et al, 2013, thus challenging the idea that the bryophytes as a clade are largely constitutively protected from desiccation.…”
Section: Life Form As An Induction Agent Of Desiccation Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates the importance of the bryophytes' life form traits, as patch size and structure, in establishing a slow dehydration rate that allows for the possibility of inductive processes of DT. A number of recent studies have indicated that the ecological strategy of DT in bryophytes is largely inducible, including both aquatic (Cruz de Carvalho et al, 2011 and desert mosses (Stark et al, 2013, thus challenging the idea that the bryophytes as a clade are largely constitutively protected from desiccation.…”
Section: Life Form As An Induction Agent Of Desiccation Tolerancementioning
confidence: 99%
“…Drying rate is crucial for DT induction in bryophytes (Stark et al, 2013;Greenwood and Stark, 2014), namely in the aquatic bryophyte Fontinalis antipyretica Hedw., where slow drying was previously shown to be essential (Cruz de Carvalho et al, 2011. The aim of the present work was to investigate how contrasting (fast and slow) dehydration rates change cell water relations in an aquatic bryophyte and how those changes explain the need for slow dehydration to induce DT.…”
Section: Introductionmentioning
confidence: 99%
“…Stark et al . ). By contrast, the desiccation‐avoiding sphagna invest in expensive structures to retain and conduct water, which enables them to maintain photosynthetic activity during drier periods.…”
Section: Introductionmentioning
confidence: 97%
“…However, such extreme phenotypes are not applicable to many plant forms and may obscure nuanced components of the process. There has been a relative paucity of research on bryophytes that show lower levels of tolerance, although some recent studies address this Cruz de Carvalho et al, 2011Pardow and Lakatos, 2013;Bader et al, 2013;Stark et al, 2013), and numerous studies have investigated moderate levels of dehydration in the drought response of vascular plants (Hsiao, 1973;Osakabe et al, 2014). Bryophytes showing moderate DhT likely occupy a large ecological niche, and understanding their response to abiotic stress is important for predicting species range shifts due to environmental changes.…”
mentioning
confidence: 99%